Globalisasi adalah mitos Sebuah kesaksian terhadap konsep globalisasi ekonomi.. Paul Hirst, Grahame Thompson ; penerjemah, P.Soemitro - HIRST, Paul; SUMITRO,P; THOMPSON, Graham (2001)
xxvi, 346 hlm ilus 21 cm